Clinical Investigations Long-term tumor control after brachytherapy for base of prostate cancer - Samuelian, Jason M.; Swanson, David A.; Kudchadker, Rajat J.; Pugh, Thomas J.; Kuban, Deborah A.; Lee, Andrew K.; Choi, Seungtaek; Nguyen, Quynh-nhu; Bruno, Teresa L.; Frank, Steven J. (Journal of Contemporary Brachytherapy, 2011)
Purpose: To evaluate the outcomes of patients presenting with cancer at the base of the prostate after brachytherapy as monotherapy. Material and methods: We retrospectively reviewed the medical records of all patients who had undergone transperineal ultrasound-guided implantation with 125 I or 103 Pd seeds as monotherapy between March 1998 and December 2006, at our institution. A minimum follow-up interval of 2 years was required for inclusion in our analysis. Dosimetry was assessed using computed tomography 30 days after the implant. Treatment failure was defined as the appearance of biopsy-proved tumor after seed implantation, radiographic evidence of metastases, receipt of salvage therapy, or elevation of the prostate-specific antigen level beyond the nadir value plus 2 ng/mL. Results : With a median follow-up interval of 89 months (range 25-128 months), all 52 of the identified patients had no evidence of disease progression or biochemical failure. The mean number of cores sampled at the prostate base was 2.84 (median 2); Gleason scores assigned at central review were 6-8 in all patients. Of the 30 patients (58%) for whom dosimetric data were available at day 30, the median V100 values of the right and left base were 92.0% and 93.5%, respectively, and the median D90 values of the right and left base were 148 Gy and 151 Gy, respectively. Conclusion : Permanent prostate brachytherapy as monotherapy results in a high probability of disease-free survival for men with cancer at the base of the prostate.